The preparation of 2,2′-bithiophene-based conjugated microporous polymers by direct arylation polymerization and their application in fluorescence sensing 2,4-dinitrophenol - Zhang, Yu-Xia (Analytica chimica acta, 2023)
In this paper, we report the synthetic strategy of direct arylation polymerization (DAP) for four 2,2′-bithiophene-based conjugated microporous polymers (the 2,2′-BTh-based CMPs) by coupling 2,2′-bithiophene with the building blocks containing bromine. Compared to conventional coupling polymerization, this synthetic scheme is simple, facile and atomically efficient owing to neither preactivating the C–H bonds in 2,2′-bithiophene using organometallic reagents nor synthesis of complex thiophene-based building blocks. The resulting 2,2′-BTh-based CMPs exhibit excellent thermal stability, high specific surface areas, and good microporosity. Their specific surface areas are higher than that of other previously reported CMPs prepared with DAP. The four 2,2′-BTh-based CMPs can be utilized for multicolor fluorescence sensing of 2,4-dinitrophenol (DNP) with the high sensitivity and selectivity. The sensitivities appear to increase with the degree of structural distortion. [Display omitted] •The 2,2′-bithiophene-based CMPs were synthesized by DAP.•The 2,2′-bithiophene-based CMPs can fluorescence sense DNP.